The Effect of Pedaling at Different Cadence on Attentional Resources - Akaiwa, Mayu; Iwata, Koki; Saito, Hidekazu; Shibata, Eriko; Sasaki, Takeshi; Sugawara, Kazuhiro (Frontiers in Human Neuroscience, 2022)
We investigated the relationship between attentional resources and pedaling cadence using electroencephalography (EEG) to measure P300 amplitudes and latencies. Twenty-five healthy volunteers performed the oddball task while pedaling on a stationary bike or relaxing (no pedaling). We set them four conditions: 1) performing only the oddball task (control), 2) performing the oddball task while pedaling at optimal cadence (optimal), 3) performing the oddball task while pedaling faster than optimal cadence (fast), and 4) performing the oddball task while pedaling slower than optimal cadence (slow). P300 amplitudes at Cz and Pz electrodes under optimal, fast, and slow conditions were significantly lower than that under control conditions. P300 amplitudes at Pz under fast and slow conditions were significantly lower than that under the optimal condition. No significant changes in P300 latency at any electrode were observed under any condition. Our findings revealed that pedaling at non-optimal cadence results in less attention being paid to external stimuli compared with pedaling at optimal cadence.